Peraturan Zonasi: Peran Dalam Pemanfaatan Ruang dan Pembangunan Kembali di Kawasan Rawan Bencana Kasus: Arkadelphia City, Arkansas USA - K Korlena; Achmad Djunaedi; Leksono Probosubanu; Nurhasan Ismail (Faculty of Engineering, Universitas Gadjah Mada, 2011)
Earthquake, tsunami and volcanic eruption are some of the various disasters that frequently hit in Indonesia. These disasters impact damage from small to large. These disasters also have a major impact on the balance of community lifes who are victims. Various efforts of reconstruction, rehabilitation and reconstruction are undertaken by governments, communities and various stakeholders. To succeed as expected, these efforts should be based an a spatial plan which is suitable and comprehensive. The spatial planning in disaster prone areas is indispensable in dealing with disasters before, during and after a disaster. Formulation and implementation of spatial plans are turned to face many problems such as limited and the loss of data due to disasters, as well as social and cultural conditions in disaster prone areas. To streamline the implementation of spatial plans and land use control need zoning regulation as a land use control instrument. Therefore, it is necessary to study the role of zoning regulation in the utilization of space and rebuilding in disaster areas prone.This study used a descriptive approach with literature sources. The results show that: (1) The Making of spatial plan on the basis of disaster mitigation in disaster prone areas is indispensable in dealing with disasters, before, during and after a disaster and should be complemented with zoning regulations, (2) The making of spatial plan and zoning regulations in the region after the disaster requires a special approach by modifying the normal procedure, and (3) zoning regulation as a land use control instrument control instrument guides the implementation of various activities related to disaster mitigation and need to be adjusted to the social, economic, cultural and characteristics of each disaster prone areas.Keywords : spatial plan, zoning regulation, disaster prone areas, disaster mitigation.